Analisis Pengendalian Persediaan Bahan Baku Serbuk Gergaji Kayu (Studi Kasus di Oka Jamur Bali, Desa Penarungan, Kecamatan Mengwi, Kabupaten Badung) - AGUSTINI CITRA DEWI; RATNA KOMALA DEWI; I KETUT SUAMBA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2016)
Analysis of Raw Material Inventory Control on the Wood Sawdust(Case Study on Mushroom Oka Bali, Penarungan Village, Mengwi District,Badung Regency)The raw material is an important factor that should be utilized effectively andefficiently. Raw materials that are not available will result the production processwould not be possible. This study aims to determine the amount of raw materialinventory control efficiency in implementing the company raw material inventorycontrol systems are effective. Economic Order Quantity method that should be doneby the company is 15,64 ton, with six times frequency in year of ordering rawmaterial, and the exact reorder point for company is 1,29 ton. The results showedthat the total cost of inventory in the Economic Order Quantity method of Rp1.652.039,00; so that savings are Rp 489.565.00. The suggestions that the authorsrecommend is 1) Oka Mushroom Bali in procuring raw material wood sawdust,should make purchases in large numbers and with a low frequency per productionperiod , this is done with the aim to minimize inventory costs that will be incurredby the company; and 2) companies should determine the magnitude of Safety Stockand the Reorder Point appropriately in the inventory control of raw materials toprotect or preserve the possibility of a shortage or excess materials and preventdelays in raw material ordered.